(untitled) (International journal of artificial intelligence, 2024)
Chronic tonsillitis is a persistent inflammatory condition of the tonsils, which can lead to recurrent infections, throat discomfort, and systemic complications if left untreated. This article reviews the latest advancements in the treatment of chronic tonsillitis, highlighting both conservative and surgical interventions. Modern treatment methods emphasize a combination of medical therapies, such as the use of antibiotics, probiotics, and immunomodulatory agents, alongside physical therapies like laser treatment and cryotherapy. For patients unresponsive to conservative treatment, surgical options, primarily tonsillectomy, remain the definitive solution. The article also explores minimally invasive techniques that reduce postoperative recovery time and complications. Current research suggests an integrative approach that tailors treatment to the severity of the condition, patient age, and underlying health conditions, aiming for improved patient outcomes and a reduction in recurrence rates.